Design and thermophysical characterization of new thermal insulation panels based on cardboard waste and vegetable fibers. (December 2021) - Benallel, Abderrahim; Tilioua, Amine; Ettakni, Mahmoud; Ouakarrouch, Mohamed; Garoum, Mohamed; Ahmed Alaoui Hamdi, Moulay
Abstract: The primary objective of this study is to develop and characterize from cardboard waste and plant fibers new thermal insulation materials. For this purpose, we used separately four different types of agricultural by-products available in abundance in the Drâa-Tafilalet region (reed, alfa, fig branches and olive leaves) with different mass fractions of cardboard waste (20%, 30%, 40%, 50% and 60%). An analysis of the microstructure of the different fibers was performed using SEM, FT-IR and X-ray diffraction analysis. Thermal conductivity was determined using the high insulation thermal house method. In addition, the water absorption rate was also determined. The results of SEM analysis showed that the fiber sizes are irregular with the presence of various filaments, certain impurities, as well as small cells or pores in the fibers. However, the results of the infrared and XDR measurements showed the presence of a crystalline cellulose phase. The increase in fiber content resulted in a slight increase in bulk density and thermal conductivity while the maximum rate of water absorption decreased significantly. The lowest thermal conductivity value is 0.072 W/m.K corresponding to a density of 176 kg/m 3 and a maximum water absorption rate of 262% was measured for the composite composed of 40% alfa fibers and 60% cardboard waste. In addition, the optimal range of our thermal insulation located between 0.072 and 0.98 W/m.K. The measured properties have shown that our composites have good insulating properties compared to conventional insulation materials; they also have several environmental and economic advantages.